Evaluation of fractional integrals involving Fox's H-Function - Luque, Rafael; Galué, Leda (Rev. Téc. Fac. Ing. Univ. Zulia, 1970)
In this paper we evaluate some fractional integrals involving the Fox's H-function of different arguments. To this end we use the multiple Wright-Erdélyi-Kober operators of Riemann-Liouville and Weyl type, defined and studied by L. Galué, S. L. Kalla and H. M. Srivastava. These operators are further generalization of the multiple Erdélyt-Kober operators, introduced and studied by V. Kiryakova and S. Kalla and involving H-functions of same nature as kernel. Fractional integrals containing the Fox's H-function have been also evaluated by M. Saigo, R. K. Saxena and J. Ram using the operators defined by M. Saigo.